Modeling longitudinal changes in maximal-intensity exercise performance in young male rowing athletes - Mikulic, P.; Blazina, T.; Nevill, A. M.; Markovic, G. (Pediatric Exercise Science, 2012)
The purpose of the current study was to examine the effect of age and body size upon maximal-intensity exercise performance in young rowing athletes. Male participants (n = 171) aged 12-18 years were assessed using an "all-out" 30-s rowing ergometer test, and reassessed after 12 months. The highest rate of performance development, which amounts to [mean(SD)] +34%(23%) and +32%(23%) for mean and maximal power output, respectively, is observed between the ages of 12 and 13, while this rate of development gradually declines as the athletes mature through adolescence. Performance increases with body size, and mass, stature and chronological age all proved to be significant (all p < .05) explanatory variables of mean power output, with respective exponents [mean(SE)] of 0.56(0.08), 1.84(0.30) and 0.07(0.01), and of maximal power output, with respective exponents of 0.54(0.09), 1.76(0.32) and 0.06(0.01). These findings may help coaches better understand the progression of rowing performance during adolescence.